Pengaruh Pesan Persuasif Oleh Penjual Melalui Live Streaming Shopee Dalam Menarik Minat Pembeli Untuk Checkout - Mulia, Rakhma Prima; Salman, Salman (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2024)
This study aims to investigate the influence of persuasive messages conveyed by sellers through live streaming on the Shopee online shopping platform on buyers interest in proceeding to checkout. This phenomenon is the subject of research due to the rapid growth of e-commerce and the popularity of live streaming media on platforms like Shopee. This research employed a quantitative approach, collecting data from a sample of buyers who participated in live streams by sellers on Shopee. Data was collected through an online questionnaire that focused on buyers perceptions of the persuasive messages delivered by sellers via live streaming and the extent to which these messages influenced their interest in proceeding to checkout. The results of this study reveal that effective persuasive messages delivered by sellers through live streaming can significantly enhance buyers interest in proceeding to checkout. Persuasive communication, encompassing product promotions, direct interaction with buyers, providing additional information, and creating emotional appeals, can exert a positive influence on buyers decisions to make a purchase. These findings offer valuable insights for sellers and e-commerce platforms like Shopee in designing more effective marketing strategies through live streaming. Sellers can optimize their persuasive messages to maximize buyers interest in proceeding to checkout, while e-commerce platforms can provide technical support and promotions to facilitate the more effective use of live streaming